Analysis of Learning Interest using Canva Media in High School Students' Indonesian Language Learning - Nur Yuliasih; Sobari, Teti; Mustika, Ika (JLER (Journal of Language Education Research), 2025)
The current development of technological life has a serious impact on various aspects of life, one of which is education. In 21st-century learning, it is important to package learning innovatively so that it is not monotonous and avoids the memorization method that was dominant in education in the past. This research was carried out to determine and describe the optimization of the Canva application as a learning medium for students' learning interests. The qualitative descriptive research method, the data collection technique was carried out using a saturated sampling technique. Class This research collects data using a non-test approach, namely through questionnaires, which aims to collect information related to students' learning interest in Indonesian language subjects. The data is processed and analyzed by taking the average of the percentage of student responses for each statement in the questionnaire. The research results show that using the Canva application for learning videos is very suitable for learning Indonesian, especially in the material of constructing observation report text which requires in-depth understanding. This statement is strengthened by questionnaire data which informs that the majority of students show attention, interest, and feelings of enjoyment with almost all students' involvement in learning.